Face Recognition Technique for Attendance Management System - Khalid, Muhammad Arif Akmal (Universiti Teknologi PETRONAS, 2017)
Attendance is crucial to track the presence of students especially in Universiti Teknologi PETRONAS because they need to achieve the minimum percentage of attendance to sit for a final examination. The lecturer needs to call the name of the students to ensure they are attending the class but it will consume longer time to finish the job. So, the lecturer will pass the attendance sheet to the students so that they will mark the attendance on their own. The problem arises when the students will try to cheat by asking their friends to put the signature on behalf of themselves. Thus, a reliable attendance management system is needed to solve this problem. The aim of this project is to develop a system that is able to mark the attendance for the students by recognizing the face. There are four main stages to develop this system. First, the user’s face need to be detected by the system.